MENINGKATNYA KESADARAN HUKUM MASYARAKAT DALAM MELAKUKAN PENDAFTARAN TANAH WARISAN ”(STUDI PADA KANTOR PERTANAHAN KOTA STABAT) - CYNTIA CECILIA (PREMISE LAW JURNAL, 2016)
It is not so easy to achieve a peaceful condition in a family life because there will always be a small problem which can become a big one between a   husband and a wife. If it happens, it will be a great effect like a divorce; therefore, it has to be solved immediately. A divorce, in turn, will eventually have an effect on children, joint property, family relationship, and so on. The role of a Notary is highly needed since the deed he has drawn up is final and conclusive and can accommodate the conflicting parties because after and before the divorce occurs they can have a deed drawn up by mentioning the joint property which will be divided evenly or not. An extra action from the court is needed in making the verdict since joint property is very complicated. The problem is that before the verdict is made, the source of data about the property, whether it has been bought during the marriage or before the marriage. By considering these data, the court can make a verdict on the case of the joint property, whether it is a real joint property or not